Cytokines in the Pathogenesis of Atherosclerosis - Young, James L.; Libby, Peter; Schönbeck, Uwe (Thrombosis and Haemostasis, 2002)
Research during the last two decades established atheromatous lesions as active sites of inflammation and immune responses, contrasting to the traditional view of atherosclerosis as an acellular lesion composed of lipid deposits. In particular, cytokines appear to orchestrate the chronic development of atherosclerosis, eventually leading to the formation of complex atherosclerotic plaques, which can trigger acute thromboembolic complications, such as myocardial infarction or stroke. Indeed the rupture-prone plaque, characterized by a thin fibrous cap overlaying a voluminous lipid core, exhibits accumulation of various pro-inflammatory cytokines. These cytokines may control the clinical consequences of plaques by mediating infiltration and accumulation of immunocompetent cells, directing the turnover of fibrillar collagens (governing the fragility of the fibrous cap), or enhancing foam cell formation and thrombogenicity of the lipid core, among other processes outlined in this review. Thus, understanding the role of cytokines in the pathophysiology of the atherosclerotic plaque might provide a promising therapeutic avenue for this prevalent human disease. This review will focus on members of the interleukin, tumor necrosis factor, and interferon families of cytokines in modulating key processes of atherogenesis.
Keywords: Atherosclerosis; inflammation; interleukin; tumor necrosis factor; interferon